Approach to design practice based on collaborative platforms: application to bicycle mobility system in Porto - Sampaio, João Nunes (2015)
This research aims to create collaborative strategies and operative tools for design practice, applied in an urban sustainable mobility scenario. We find that co-creation platforms encourage an active approach involving the people in the development process leading to effective and holistic solutions. Initially we catalogued tools and collaborative met hods based on case studies, to identify and propose new approaches to various project phases, action modes, creation, development, testing and implementation of proposals. Through action-research methods we want to validate a toolkit applied in developing a bicycle mobility system in Porto (Portugal). Designers, users and stakeholders actively collaborated defining a real context of action, developing and implementing solutions. Started by a bottom-up approach, bringing together groups of city cyclists and sustainable mobility activists, and then the local authorities, the project enabled positive and local impact based on a democratic design approach. The replicative potential of this action model is a next challenge to various application scenarios.